2005
DOI: 10.1016/j.jpain.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Behavioral Pain Management to Healthcare Professionals: A Systematic Review of Research in Training Programs

Abstract: Pain is a common and potentially debilitating condition. Whereas there is vast literature on developmentally appropriate behavioral techniques for pain management, results of curriculum evaluations and knowledge surveys reveal a dearth of awareness of these strategies in healthcare professionals. As a result, the development and evaluation of pain management training programs is an important endeavor. Results of studies evaluating such programs are promising and suggest that training may be an effective means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The long-term benefit of effective pain management could also increase revenue for the hospital, as patients may be discharged earlier (MacLaren & Cohen, 2005). Perhaps workshops could be organised for specialties to ensure depth of information and this could increase applicability of the knowledge gained.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term benefit of effective pain management could also increase revenue for the hospital, as patients may be discharged earlier (MacLaren & Cohen, 2005). Perhaps workshops could be organised for specialties to ensure depth of information and this could increase applicability of the knowledge gained.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the next iteration of the OUCH card will include the revised Face, Leg, Activity, Cry, Consolability Scale observational pain tool, which shows improved reliability and validity for pain assessment in children with cognitive impairment. 39 Finally, determining best practices for the most efficient and cost-effective means of delivering pain management education is a greatly needed step 40 that may be discernible in subsequent studies. The effect of lecture versus OUCH card distribution (as well as their combination) merits further investigation in order to better understand the optimal content and format of training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-based simulations provide a significant number of learning affordances that can help change nursing students' attitudes and behaviors toward and practice of pain assessment and management. Ó 2015 by the American Society for Pain Management Nursing BACKGROUND Pain is frequently an initial symptom in emergency department (ED) patients (Baharuddin, Mohamad, Nik Abdul Rahman, Ahmad, & Nik Him, 2010;Bergman, 2012;Clarke et al, 1996;Downey & Zun, 2010;Hogan, 2005;MacLaren & Cohen, 2005;Paulson-Conger, Leske, Maidl, Hanson, & Dziadulewicz, 2011;Plaisance & Logan, 2006;Safdar et al, 2009;Shaban, Holzhauser, Gillespie, Huckson, & Bennetts, 2012;Simpson, Kautzman, & Dodd, 2002;Tanabe & Buschmann, 1999, 2000. Recent research studies found pain to be present in 60% to 90% of patients arriving in EDs (Baharuddin et al, 2010;Bergman, 2012;Downey & Zun, 2010;Fry, Holdgate, Baird, Silk, & Ahern, 1999;Hogan, 2005;Tanabe & Buschmann, 2000;Thomas, 2007;Wilsey, Fishman, Ogden, Tsodikov, & Bertakis, 2008).…”
Section: Pain Assessment and Management In Nursing Education Using Comentioning
confidence: 99%
“…Children with pain can experience emotional difficulties, disruption in school attendance, and impaired social skills (MacLaren & Cohen, 2005;Rutledge & Caple, 2011). Additionally, depending on the cultural norms, patients of different ethnic groups will be more or less verbally expressive about their pain (Rutledge & Caple, 2011).…”
Section: Pain Assessment and Management In Nursing Education Using Comentioning
confidence: 99%